Ecotourism Management and Economic Valuation of the Bahowo Mangrove Area: A Strategy for Revitalization into a Sustainable Tourism Destination - Oktavianus Lintong; Jeanlly A. Solang; Meiske M. Sangian; Easter Ch. M. Tulung (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The Bahowo mangrove ecotourism area in Manado City has declined in economic and ecological value after its functional shift to a transit dock. This condition contradicts the principles of a sustainable tourism destination, which demands a balance among ecological, economic, and socio-institutional aspects. This study intends to evaluate existing conditions and formulate an ecotourism management strategy, grounded in economic valuation, integrity tourism, and the heptahelix model, to revitalize Bahowo as a sustainable tourism destination. The research approach combines physical carrying capacity analysis with the Contingent Valuation Method (CVM) to measure visitors' Willingness to Pay (WTP). The results show that the resource suitability level is classified as